The Caricom-Canada FTA : what's the hurry? - Girvan, Norman ([s.n.] [S.l.], 2009)
Provides several reasons why it will not be wise for Caricom to rush into a Caricom-Canada FTA, especially in light of the deepening global financial and economic crisis.